The Influence of Viral Marketing, Online Customer Reviews, and Price on Purchasing Decisions on Skintific Skincare Products in the Tiktokshop Marketplace. - pramesti, Zulia ika wahyu; kusumaningtyas, Dian (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research purposes : This study intends to: 1) evaluate the effect of viral marketing on purchasing decisions on skintific skincare items in the tiktok store marketplace. 2) evaluate the effect of online customer reviews on purchasing decisions on skintific skincare items in the tiktok store marketplace. 3) ascertain how pricing affects decisions to buy skintific skincare goods in the marketplace of the TikTok shop. 4) ascertain how costs, online customer reviews, and viral marketing affect consumers' decisions to buy skintific skincare goods from the tiktok store marketplace.Approach/Method/Design  : This study employed a quantitative methodology, using a survey method with 97 respondents as the sample size, meeting the following requirements: Customers who have bought skintific skincare products from the Tiktok store. Sampling was determined using the techniquenon probability sampling. Data analysis through using SPSS software version 25 to perform multiple linear regression analysis. Research Findings: The findings of the first hypothesis research show that, in the Tiktok store marketplace, viral marketing significantly influences consumers' decisions to buy skintific skincare goods. The second hypothesis demonstrates that in the Tiktok shop marketplace, online customer reviews significantly influence consumers' decisions to buy skintific skincare items. The third hypothesis demonstrates that, in the Tiktok shop marketplace, price significantly influences consumers' decisions to buy skintific skincare goods. In the Tiktok store marketplace, the fourth hypothesis demonstrates that costs, online customer evaluations, and viral marketing significantly influence consumers' decisions to buy skintific skincare items.Theoretical contribution / Originality :This research has a role in developing purchasing decision theory and providing more detailed knowledge about what factors can influence consumer purchasing decisions.Practitioner/Policy Implications:This research adds insight for business actors in improving marketing, getting the best reviews from customers in the marketplace, and determining affordable prices. The results of this study can be used in developing businesses to make consumers interested in buying.Research limitations:The limitations of this study are that viral marketing factors, online customer reviews, and prices only contribute 56.4% to the decision to purchase Skintific skincare on the Tiktok shop, so there are still other factors that can influence purchasing decisions.